Outsourcing Security and the Reconfiguration of State Power After the Arab Uprisings - Moussa, Engy (Cranfield University, 2020)
This research explores how increased privatization and outsourcing of security in some Arab countries since the 2010-2011 uprisings has contributed to the reconfiguration of state power and the survival of authoritarian rule. This enquiry is pursued in two case studies: Egypt and Tunisia. The considerable historical and contemporary similarities between both countries offer rich grounds for comparative analysis while the particularities of each case present unique elements of analysis and grounds to draw different conclusions to test in other cases.While acknowledging the neo-liberal roots of the current expansion of the private security industry in the Arab region, this research argues that this development essentially fits into an ongoing framework of authoritarian adaptation pursued by the Arab region’s ruling regimes to ensure their survival and prosperity. This manifests through the provision of alternative agents and strategies for social control alongside new venues to expand regime interests.
Keywords: 'DSDS20 Poster'; 'DSDS20'; 'Private security'; 'Middle East'; 'Authoritarianism'; 'Private Policing and Security Services'